2016
DOI: 10.1186/s12879-016-1597-9
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid in tuberculous meningitis exhibits only the L-enantiomer of lactic acid

Abstract: BackgroundThe defining feature of the cerebrospinal fluid (CSF) collected from infants and children with tuberculous meningitis (TBM), derived from an earlier untargeted nuclear magnetic resonance (NMR) metabolomics study, was highly elevated lactic acid. Undetermined was the contribution from host response (L-lactic acid) or of microbial origin (D-lactic acid), which was set out to be determined in this study.MethodsIn this follow-up study, we used targeted ultra-performance liquid chromatography–electrospray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…(3) Lactic acid is a key intermediate in many biochemical processes and is a measure of critical illness in patients with poor prognosis. It may be of endogenous (L-lactate) or exogenous (D-lactate) origin and we recently proposed that the determination of its enantiomers in infectious conditions may provide a basis for substantiating the clinical significance of disease markers [29]. The presence of these exogenous markers of gut origin provides further indications of the connectivity between disturbances in the gut microbial populations and the metabolic consequences of the altered microbial–mammalian metabolic balance influencing host disease, which will be discussed below in the context of FMS.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…(3) Lactic acid is a key intermediate in many biochemical processes and is a measure of critical illness in patients with poor prognosis. It may be of endogenous (L-lactate) or exogenous (D-lactate) origin and we recently proposed that the determination of its enantiomers in infectious conditions may provide a basis for substantiating the clinical significance of disease markers [29]. The presence of these exogenous markers of gut origin provides further indications of the connectivity between disturbances in the gut microbial populations and the metabolic consequences of the altered microbial–mammalian metabolic balance influencing host disease, which will be discussed below in the context of FMS.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Mason et al. demonstrated that the increase in lactate levels commonly observed in the CSF of patients who go on to develop poor outcomes is of the L‐form and therefore solely a response from the host to the infection, rather than being of microbial origin . This finding contributes to this groups’ hypothesis that in the context of neuroinflammatory‐inducing infection, energy flow in brain metabolism is shifted away from the neurons and shunted toward the microglia.…”
Section: Pathogenic and Pathophysiologic Mechanisms Within The Brain mentioning
confidence: 99%
“…Host-derived terminal glycolytic products such as pyruvate and L-lactate (lactate) have been under investigated in the context of Mtb infection. Pyruvate and lactate are commonly found reaching μM and mM concentrations in blood, muscle and epithelial mucosa as well as in cerebrospinal fluid (Zhang and Natowicz, 2013;Gu et al, 2014;Mason et al, 2016). Importantly, production and secretion of lactate increases during inflammation as a consequence of the switch from oxidative to fermentative metabolism (Kelly and O'Neill, 2015) and this phenomenon clearly occurs during macrophage infection by Mtb (Somashekar et al, 2011;Shi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%